Numerical simulation of cold-formed T-shaped built-up steel sections under bending. (2021) - Aruna, G.; Ponraj Sankar, L.; Sudharsan, N.; Balakrishnan, V.
Abstract: In the Cold-Formed Steel (CFS) structural construction, the usage of built-up beam sections are increasing gradually. The demand for cold-formed steel sections is being increased. Hence it leads to the development of innovative and cost-effective built-up beam sections. This paper describes the flexural behaviour of innovative built-up CFS T shaped sections with intermediate stiffeners on the web. Three specimens were taken and tested under the two-point loads. A coupon tensile test was carried out to determine the properties of the material. A non-linear finite element model was developed and verified with the experimental results. It was observed that moment carrying capacity and failure modes obtained from the Finite Element Analysis (FEA) was correlated well with the experimental results. The effect of variation of thickness and length on the flexural capacity of the specimen was investigated using a verified finite element model.